The “Trinity” smart hospital construction policy promotes the development of hospitals and health management in China - Zhang, Guang-Wei; Gong, Mengchun; Li, Hui-Jun; Wang, Shuang; Gong, Da-Xin (Frontiers in Public Health, 2023)
Recently, in order to comprehensively promote the development of medical institutions and solve the nationwide problems in the healthcare fields, China's government developed an innovative national policy of "Trinity" smart hospital construction, which includes "smart medicine", "smart services" and "smart management". The prototype of evaluation system has been established, and large numbers of construction achievements have emerged in many hospitals. In this article, the summary for this field was performed to provide a reference for medical workers, managers of hospitals, as well as policy makers.